Child Protection in Islamic Contexts: Identifying Cultural and Religious Appropriate Mechanisms and Processes Using a Roundtable Methodology. (3rd April 2014) - Hutchinson, Aisha Jane; O'Leary, Patrick; Squire, Jason; Hope, Kristen
Abstract : This paper reports on a piece of research which brought together eight Islamic scholars, four child protection academics and two international development agencies to identify mechanisms and processes which safeguard children from harm that are congruent with Islamic scholarship and practices. Roundtable methodology was used to share knowledge, build networks and increase engagement with child protection by bringing together different stakeholders to share experiences and encourage collaboration in a relatively cost‐effective manner. Four key themes were identified following initial qualitative data analysis of the roundtable discussion: (1) The convergence and divergence in Islamic thought on issues of child protection; (2) knowledge sharing and partnership working; (3) individual and collective wellbeing; and (4) mechanisms and tools for intervention. Findings from the roundtable indicate that a reliance on solely Western‐based models does not allow for the trust and credibility that enable intervention at a deeper level in Islamic communities. Critically, the roundtable highlighted a significant gap in how Islamic knowledge and principles are practically applied to child protection policy and practice in international development contexts. Next steps are identified for building a knowledge base that can be practised in Islamic communities. Copyright © 2014 John Wiley & Sons, Ltd. 'Bringing together different stakeholders to share experiences and encourage collaboration in a relatively cost‐effective manner' Key Practitioner Messages: Religious communities are invaluable partners for protecting children and enhancing wellbeing. Despite clear guidance from the Quran and the Sunna about the principles of child protection in Muslim communities, local customs and socio‐political contexts can challenge their application. Mutual learning and shared knowledge between child protection actors and religious actors is key. Community harmony needs to be considered alongside individual experiences within families. Mistrust of 'outsiders' is a significant barrier to engaging with organic child protection mechanisms in Islamic contexts.